The risk of oesophago-gastric cancer in symptomatic patients in primary care: a large case-control study using electronic records. - Stapley, S; Peters, T; Neal, R; Rose, P; Walter, F; Hamilton, W (2013)
BACKGROUND: Over 15 000 new oesophago-gastric cancers are diagnosed annually in the United Kingdom, with most being advanced disease. We identified and quantified features of this cancer in primary care. METHODS: Case-control study using electronic primary-care records of the UK patients aged ≥40 years was performed. Cases with primary oesophago-gastric cancer were matched to controls on age, sex and practice. Putative features of cancer were identified in the year before diagnosis. Odds ratios (ORs) were calculated for these features using conditional logistic regression, and positive predictive values (PPVs) were calculated. RESULTS: A total of 7471 cases and 32 877 controls were studied. Sixteen features were independently associated with oesophago-gastric cancer (all P<0.001): dysphagia, OR 139 (95% confidence interval 112-173); reflux, 5.7 (4.8-6.8); abdominal pain, 2.6 (2.3-3.0); epigastric pain, 8.8 (7.0-11.0); dyspepsia, 6 (5.1-7.1); nausea and/or vomiting, 4.9 (4.0-6.0); constipation, 1.5 (1.2-1.7); chest pain, 1.6 (1.4-1.9); weight loss, 8.9 (7.1-11.2); thrombocytosis, 2.4 (2.0-2.9); low haemoglobin, 2.4 (2.1-2.7); low MCV, 5.2 (4.2-6.4); high inflammatory markers, 1.7 (1.4-2.0); raised hepatic enzymes, 1.3 (1.2-1.5); high white cell count, 1.4 (1.2-1.7); and high cholesterol, 0.8 (0.7-0.8). The only PPV >5% in patients ≥55 years was for dysphagia. In patients <55 years, all PPVs were <1%. CONCLUSION: Symptoms of oesophago-gastric cancer reported in secondary care were also important in primary care. The results should inform guidance and commissioning policy for upper GI endoscopy.